1981
DOI: 10.1021/bi00512a001
|View full text |Cite
|
Sign up to set email alerts
|

Crystallographic refinement and atomic models of a human Fc fragment and its complex with fragment B of protein A from Staphylococcus aureus at 2.9- and 2.8-.ANG. resolution

Abstract: The model of human Fc fragment was refined at 2.9-A resolution. Two different automated procedures for crystallographic refinement were used [Deisenhofer, J., & Steigemann, W. (1975) Acta Crystallogr., Sec. B B31, 238; Jack, A., & Levitt, M. (1978) Acta Crystallogr., Sect. A A34, 931]. The final R value is 0.22. The dimer of CH3 domains closely resembles the CH1-CL aggregate in Fab fragments. There is no contact between CH2 domains. The contact between CH2 and CH3 domains has about one-third of the size of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

48
1,061
5
3

Year Published

1996
1996
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 1,424 publications
(1,117 citation statements)
references
References 26 publications
48
1,061
5
3
Order By: Relevance
“…Though this appears to be a somewhat convoluted mechanism to explain the observations, it has been shown that there is contact between the two glycans through the two core mannose residues and that in the absence of this interaction the structure of the CH 2 domains are perturbed, highlighting the interaction between the glycans and this region of the Fc. [24][25][26] Now we consider the possibility that the effect observed was due to oxidation of Met430. Residues HC[247-253] have been shaded dark red in Figure 3, it can be seen that in the crystal structure these residues form an a-helix, which is located adjacent to methionines 253 and 430.…”
Section: Resultsmentioning
confidence: 99%
“…Though this appears to be a somewhat convoluted mechanism to explain the observations, it has been shown that there is contact between the two glycans through the two core mannose residues and that in the absence of this interaction the structure of the CH 2 domains are perturbed, highlighting the interaction between the glycans and this region of the Fc. [24][25][26] Now we consider the possibility that the effect observed was due to oxidation of Met430. Residues HC[247-253] have been shaded dark red in Figure 3, it can be seen that in the crystal structure these residues form an a-helix, which is located adjacent to methionines 253 and 430.…”
Section: Resultsmentioning
confidence: 99%
“…IgG molecules are mainly glycosylated at Asn-297 of the CH2 domain within the Fc region [3,4], with variable galactosylation but limited sialylation. The remaining glycosylation occurs in the hypervariable regions of the Fab region, with the position and frequency of occurrence being dependent on the presence of the consensus sequence Asn-Xaa-Thr/ Ser for N-glycosylation, and is characterized by a high incidence of sialylated structures.…”
Section: Introductionmentioning
confidence: 99%
“…X-Ray crystal electron density maps of the IgG-Fc revealed that the N297-linked glycan is sequestered within the internal space enclosed by the CH2 domains. There are extensive non-covalent interactions between the carbohydrate and the protein moiety, resulting in reciprocal influences on conformation [3].…”
Section: Introductionmentioning
confidence: 99%
“…As assessed by Protein A binding, antibody titers ranged from 0 to 982 mg/L. However, because the CH2 and CH3 domains form the binding interface with Protein A, 22 we anticipated that some antibody variants carrying aldehyde tags in these regions would be expressed but undetected by our Protein A-coated ForteBio sensor used for titer measurements. Accordingly, scanned regions of the CH2 domain where antibody titers were low as measured by Protein A (e.g., 188V through 206V) were tested for antibody titers by ForteBio using a Protein L-coated sensor.…”
Section: Resultsmentioning
confidence: 99%